PC Technician's Troubleshooting Pocket Reference - Bigelow, Stephen (Mcgraw-Hill Companies Inc, 2000)
Get essential PC troubleshooting and diagnostic information from this handy pocket reference. Packed with code tables, commands, symptom summaries, solutions, and other key details, this easy access guide gives you just the facts you need at your fingertips.
Keywords: Computers-Computer architecture-Hardware-Personal computers-Microcomputers-Maintenance and repair-Handbooks-Nonfiction